Analysis of Causes of Starting Failure on Auxiliary Engine MT Green Stars with HAZOP Method - Ardiansyah Nur Rahman; Shofa Dai Robbi; Akhmad Kasan Gupron; Azis Nugroho; Nasri; Rama Syahputra Simatupang; Imam Sutrisno (International Journal of Marine Engineering Innovation and Research, 2025)
Air motor starter is a component that functions to rotate the engine auxiliary flywheel to move the piston for the first combustion to occur. In this system, high-pressure air from a compressor or air tank is used to drive a starter motor that is directly connected to the engine crankshaft. As the starter motor operates, pressurized air is channeled into the starter motor cylinders, creating a rotational movement on the shaft that eventually rotates the auxiliary engine crankshaft. Air motor starters on MT Green Stars are essential for the auxiliary engine starting system on board MT Green Stars. This study aims to analyze the factors that cause the failure of auxiliary engine start failure caused by the rupture of the starter motor water bearing and the impact on the auxiliary engine. This research uses a descriptive analysis method using HAZOP data analysis techniques and data collection from observations, logbooks, journals, manual books, and interviews The research was conducted on the MT Green Stars ship which has three auxiliary engines and is experiencing problems with the starting system. Based on the research, failure factors in auxiliary engines are caused by several factors, namely starter motor water, injectors, starter motor water, and fuel filters. The impact of auxiliary engine start failure causes failure of the electrical system, system, pump, hydraulic and pneumatic system disorders, work efficiency disorders, risk of damage to the main engine, and safety and regulatory disorders. To handle it, maintenance needs to be carried out, both preventive maintenance and breakdown maintenance. The suggestions that researchers make are to routinely carry out maintenance according to PMS (Planned Maintenance System), carry out toolbox meetings, check especially auxiliary engines.